Islamic Communication Strategy of the National Narcotics Agency (BNN) in Handling Drug Abuse in South Tapanuli Regency - Wibowo, Hendro; Azhar, Anang Anas; Simamora, Irma Yusriani (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This article aims to analyze the Islamic Communication Strategy pattern of the National Narcotics Agency (BNN) in Handling Drug Abuse in South Tapanuli Regency. A descriptive qualitative approach is used in this paper. The research was conducted at the National Narcotics Agency Office of South Tapanuli Regency, Jalan Raja Inal Siregar km 5.7 Padang Sidempuan City, North Sumatra. The research period is 8 months (October 2022 - July 2023). The informants for this research were 11 employees of the National Narcotics Agency, South Tapanuli district. Data collection was carried out using the triangulation method. Meanwhile, the data analysis technique used in this research is qualitative data analysis, carried out interactively through the process of data reduction, data display (data presentation), and conclusion drawing / verification (drawing conclusions). The research results provide an answer that the Islamic Communication strategy (BNN) is implemented through three stages, namely 1) Islamic Communication with a coaching pattern, 2) Islamic Communication with an invitation, advice and guidance pattern, 3) Islamic Communication with an exemplary pattern. These three strategies are carried out through various activities, including inviting and requiring drug victims to always join in congregational prayers 5 times a day, attending congregational Friday prayers at the mosque, providing tausiah to drug victims and teaching them to be able to repent by reading verses and hadiths about the impacts and sins. using narcotics, teaching drug victims about the correct ablution, teaching drug victims the correct prayer, and learning to read the Koran